Proposing conceptual model in assessing e-commerce adoption in Iraq and Malaysia / Abdulsatar Abduljabbar Sultan, Mohamad Ghozali Hassan and Sarina Muhamad Noor. - Abduljabbar Sultan, Abdulsatar; Hassan, Mohamad Ghozali; Muhamad Noor, Sarina (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
E-commerce adoption is one of the means to remain competitive in the global market. Moreover, with the growth of information technology and suitable infrastructure, e-commerce adoption is inevitable. However, the rate of e-commerce adoption differs from one country to another. There are many factors that affect the rate of adoption. Meanwhile, many studies have concentrated in the developed and industrialized countries. Therefore, this study proposed a conceptual model of e-commerce adoption that can be applied on both Iraq and Malaysia contexts. These two countries differ in terms of governmental role, facilities available and access to internet. However, both are emerging in the quest of e-commerce transaction. The study will be underpinned by two theories, namely Diffusion of Innovation Theory (DOI) and Resource Dependence Theory (RDT). Eight factors are chosen to represent organizational, technological and environment contexts. This study offers valuable insights to managers, and policy makers who are responsible for assisting Small and Medium Enterprises) SMEs (in participating into the new paradigm business operations.